Pengelolaan Sampah Berbasis Masyarakat dalam Mitigasi Perubahan Iklim: Suatu Telaah Sistematik - Anti Ahsanti; Husen, Achmad; Samadi (Jurnal Green Growth dan Manajemen Lingkungan, 2022)
Climate change presents a major attention worldwide due to its threat to the environment. One of the contributors to climate change is greenhouse gas that elevates global temperature. Methane (CH4) is the second most important greenhouse gas after carbon dioxide. An important source of CH4 generation is anaerobic decomposition of organic municipal solid wastes (MSW) in landfill sites. Some control measures are in need to be undertaken, and reducing a number of MSW in landfill sites being one of them. Integrated Waste Management System is a systems approach that should be used as a solution to the waste problem solving. Society’s active participation is needed to create a more comprehensive system of municipal wa te management, based on “reduce, reuse, recycle” principle. The objectives of this literatur research work were to describe the development of variety research occurred with Community Based Waste Management (CBWM) systems as the alternative approach to the typical MSW management techniques reducing greenhouse gas emission.